MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA GUNUNG SARI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Nurhasan, Abdul Khodir; Rizki (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This study aims to determine the planning, implementation, and impact of Islamic microfinance institutions in Gunung Sari Village, Pamijahan District, Bogor Regency. The subject of this research is the strategic design of sharia microfinance institutions that are in accordance with the characteristics and needs of the research location, namely Gunung Sari Village. In this study, a descriptive analysis method is used to identify strategic measures and effective business models for sharia microfinance institutions at the village level. The results of this study show that designing the right sharia microfinance institution can contribute significantly to local economic development and the welfare of local communities. With this study, it can be concluded that the development of sharia microfinance institutions at the village level requires a careful, thorough and focused approach to ensure their sustainability and success.